Private Label Fashion Brands: Through the Lens of Masstige Marketing Theory - Chaudhary, Prashant; Sharma, Sarika (Indian Journal of Marketing, 2022)
The purpose of this study was to investigate the influence of private label brands (PLBs) developed and managed by fashion retailers on the loyalty of customers towards the fashion retailers. We further intended to study the significance of PLBs in terms of enhancing profitability, perceived fashion value, and loyal customer base of fashion retailers through the lens of ‘Masstige Marketing.’ This novel approach of the application of masstige marketing for designing PLB plans gives a novel strategic consideration to fashion retailers in terms of curating strategically developed PLBs for their target audience. This study dwelt upon how strategically developed PLBs – by blending the mass appeal with prestige value and image – affected loyalty behavior, perceived fashion value, and profitability. Although this qualitative research was conducted from the perspective of the Indian retail sector, the findings applied to international markets as well since the strategic considerations towards PLBs are similar in both contexts. The findings showed that the smart PLBs – built by applying masstige marketing strategies – positively impacted customers’ loyalty and brand advocacy behavior. These PLBs will also help fashion retailers to enhance their perceived fashion value and have a profound impact on profitability.